Can Literature Save Lives? Review of Maren Tova Linett, Literary Bioethics: Animality, Disability and the Human (NYU, 2020) - Quinn, Emelia (Humanimalia, 2023)
Review of: Maren Tova Linett. Literary Bioethics: Animality, Disability and the Human. Crip: New Directions on Disability Studies. New York: New York University Press, 2020. 224 pp. 28.00 (pb) ISBN: 9781479801251.